The influence of lifestyle interventions and overweight on infertility: a systematic review, meta-analysis, and meta-regression of randomized controlled trials - Sustarsic, Ana; Hadzic, Vedran; Meulenberg, Cécil J. W.; Abazovic, Ensar; Videmsek, Mateja; Burnik Papler, Tanja; Paravlic, Armin H. (Frontiers in Medicine, 2023)
The objective of this study was to investigate the impact of the lifestyle intervention (LSI) on diagnosed infertility in overweight and obese women. A systematic review and meta-analysis was conducted. A literature search was performed using the following databases from September 2022 to December 2022: PubMed, Web of Science, and SPORTDiscus. The inclusion criteria were the following: women between 18 and 45 years of age, BMI over 25.0 kg/m 2 , diagnosed with infertility, a weight loss intervention and control group part of RCTs. In total, 15 studies were identified and included. The metaanalysis shows a beneficial effect of LSI on reducing weight, waist circumferences, and BMI as well as management onincreasing infertility. A significantly beneficial effect of lifestyle intervention on BMIweight reduction was observed for participants who had initially higherlower BMI, while a nonsignificant effect was observed for obese individuals with BMI above 35 kg/m 2 . The meta-analysis showed a beneficial effect of lifestyle intervention on ovulation incidence and sex hormone-bindin g globulin., respectively. The lifestyle intervention group had 11.23 times more ovulatory incidence than the control group, which in turn increased the ability to conceive. As robust evidence for the impact of lifestyle intervention on infertility in obese and overweight women was found, and it is advised to integrate similar interventions in future infertility treatment processes.